Reactivation of des(119-, 120-, or 121–124) Ribonuclease A by Mixture with Synthetic COOH-terminal Peptides of Varying Lengths - Bernd Gutte; Michael C. Lin; D. G. Caldi; R. B. Merrifield (1972)
Abstract The COOH-terminal tetradecapeptide of bovine pancreatic ribonuclease A, Glu-Gly-Asn-Pro-Tyr-Val-Pro-Val-His-Phe-Asp-Ala-Ser-Val, and a series of shorter peptides containing 7 to 12 amino acid residues from the carboxyl terminus were synthesized by the solid-phase method. The peptides were examined for their ability to restore the enzymatic activity of ribonuclease A from which the last four, five, or six amino acids had been removed. The hepta- and octapeptides only regenerated 1 to 2% activity when mixed with RNase 1–118, but the activity increased sharply to 60% when the peptide was extended to a length of 9 residues by the addition of Val116. The activity increased gradually with increasing chain length and reached a maximum of 98% at the tetradecapeptide stage. Qualitatively similar reactivation of RNase 1–119 and RNase 1–120 was observed. The His119 residue in RNase 1–119 was found to compete with His119 of the synthetic peptides for contribution of a functional histidine residue to the active site of the reconstituted enzyme. The results of alkylation by iodoacetate showed that there are two enzymatically active forms of the combination product.